Pengaruh Pola Asuh Islami terhadap Kenakalan Remaja - Muhammad Rifald; Zahro Varisna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
parenting is the attitude and behavior of parents towards children from an early age, from the stage of teaching, developing, adapting and educating children referring to the Qur'an and al-Hadith (Asuh et al., 2017). The Islamic parenting style provided by parents also has an impact on children's behavior so that it can trigger good or bad behavior in a child, this can influence the occurrence of juvenile delinquency. This research aims to identify the influence of Islamic parenting on juvenile delinquency. The method used was quantitative correlation by collecting data through a questionnaire using a gform link which was distributed to 123 respondents aged 10-24 years. The sampling technique applied is accidental sampling. Data analysis was carried out using Product Moment correlation with SPSS version 23. The results showed that the correlation coefficient was negative, namely -0.514, so the correlation between the two variables was inverse so that the higher the Islamic parenting style, the lower the juvenile delinquency. the higher the rate of juvenile delinquency.